Arah Baru Manajemen Produksi: Pergeseran Paradigma Menuju Manufaktur Yang Tangguh, Berpusat Pada Manusia, Dan Berkelanjutan Di Tengah Disrupsi Industri 5.0 - Febriyanti Jumat; Wahyuddin .; Mahfudnurnajamuddin .; Suriyanti . (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
In the era of Industry 5.0, Production Management (PM) faces major challenges due to technological disruption and increasing demands for sustainability. This situation requires manufacturing to become more resilient, human-centered, and focused on long-term sustainability.This study aims to describe the paradigm shift, main focus, and current challenges in PM, as well as to identify the relationship between student satisfaction, learning motivation, and academic achievement.The research uses a Systematic Literature Review (SLR) with a qualitative approach, collecting data from reputable journal articles and analyzing them thematically to identify patterns, consensus, and theoretical gaps. Findings show that modern PM has shifted from a narrow focus on cost optimization to a model that balances efficiency (Lean Manufacturing) and flexibility (Agile Manufacturing). Success in PM relies on integrating Total Quality Management (TQM), adopting Cyber-Physical Production Systems (CPPS) and Big Data Analytics, and strengthening Supply Chain Resilience.The study encourages the development of a Lean-Agile-Green model that integrates sustainability and social ethics as key dimensions of PM. Organizations are urged to pursue holistic digital transformation, invest in data-driven workforce upskilling, and plan strategically to balance cost efficiency and network resilience.